Individual HLA-A, -B, -C, and -DRB1 Genotypes Are No Major Factors Which Determine COVID-19 Severity - Schetelig, Johannes; Heidenreich, Falk; Baldauf, Henning; Trost, Sarah; Falk, Bose; Hoßbach, Christian; Real, Ruben; Roers, Axel; Lindemann, Dirk; Dalpke, Alexander; Kolditz, Martin; de With, Katja; et al. (Frontiers in Immunology, 2021)
HLA molecules are key restrictive elements to present intracellular antigens at the crossroads of an effective T-cell response against SARS-CoV-2. To determine the impact of the HLA genotype on the severity of SARS-CoV-2 courses, we investigated data from 6,919 infected individuals. HLA-A, -B, and -DRB1 allotypes grouped into HLA supertypes by functional or predicted structural similarities of the peptide-binding grooves did not predict COVID-19 severity. Further, we did not observe a heterozygote advantage or a benefit from HLA diplotypes with more divergent physicochemical peptide-binding properties. Finally, numbers of in silico predicted viral T-cell epitopes did not correlate with the severity of SARS-CoV-2 infections. These findings suggest that the HLA genotype is no major factor determining COVID-19 severity. Moreover, our data suggest that the spike glycoprotein alone may allow for abundant T-cell epitopes to mount robust T-cell responses not limited by the HLA genotype.